Identification of a novel spinal nociceptive-motor gate control for Aδ pain stimuli in rats - Dvir Blivis; Gal Haspel; Philip Z Mannes; Michael J O'Donovan; Michael J Iadarola (eLife, 2017)
Physiological responses to nociceptive stimuli are initiated within tens of milliseconds, but the corresponding sub-second behavioral responses have not been adequately explored in awake, unrestrained animals. A detailed understanding of these responses is crucial for progress in pain neurobiology. Here, high-speed videography during nociceptive Aδ fiber stimulation demonstrated engagement of a multi-segmental motor program coincident with, or even preceding, withdrawal of the stimulated paw. The motor program included early head orientation and adjustments of the torso and un-stimulated paws. Moreover, we observed a remarkably potent gating mechanism when the animal was standing on its hindlimbs and which was partially dependent on the endogenous opioid system. These data reveal a profound, immediate and precise integration of nociceptive inputs with ongoing motor activities leading to the initiation of complex, yet behaviorally appropriate, response patterns and the mobilization of a new type of analgesic mechanism within this early temporal nociceptive window.